1997
DOI: 10.1111/j.1600-0412.1997.tb07987.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality after cesarean section in The Netherlands

Abstract: Although cesarean section is a relatively safe procedure nowadays, birth by cesarean section in The Netherlands is seven times more hazardous than vaginal birth. Keeping the cesarean birth rate as low as possible is therefore in the interest of women of reproductive age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(74 citation statements)
references
References 6 publications
1
67
1
5
Order By: Relevance
“…Particularly relevant for women not receiving any antiretroviral therapy would be a discussion of the randomized trial evidence for a substantial reduction in transmission risk associated with prophylactic cesarean delivery. However, we would further counsel these women that cesarean delivery is associated with an increased risk of maternal morbidity and mortality in immunocompetent women 41 and that this risk is likely potentiated by HIV infection. Thus, for women not receiving antiretroviral medication, we would offer short-course antiretrovirals as an alternative intervention of proven efficacy.…”
Section: Counseling Pregnant Women With Hiv Infectionmentioning
confidence: 95%
“…Particularly relevant for women not receiving any antiretroviral therapy would be a discussion of the randomized trial evidence for a substantial reduction in transmission risk associated with prophylactic cesarean delivery. However, we would further counsel these women that cesarean delivery is associated with an increased risk of maternal morbidity and mortality in immunocompetent women 41 and that this risk is likely potentiated by HIV infection. Thus, for women not receiving antiretroviral medication, we would offer short-course antiretrovirals as an alternative intervention of proven efficacy.…”
Section: Counseling Pregnant Women With Hiv Infectionmentioning
confidence: 95%
“…Maternal mortality is greater after caesarean than vaginal delivery (Frigoletto 1980;Lilford 1990;Schuitemaker 1997), though it is difficult to be sure to what extent this is due to the operation or to the reason for the operation. Transient tachypnoea of the newborn is more common after caesarean section, and birth trauma is not eliminated (Nielsen 1984).…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…This would equate to a maternal death rate of 1 in 4262 for mothers having elective caesarean section which seems high, particularly compared with unproven claims of avoidable intrapartum fetal death. A more recent study from The Netherlands 4 found a similar relative risk of 3.25 (and a death rate of 13/100,000). Extrapolated estimates (Table 1) show that elective caesarean section death rates can be as much as two to eight times higher 5 , and in the 1994 -1996 Confidential Enquiry period would be at least three times higher 6 , than vaginal delivery.…”
mentioning
confidence: 78%